THE INFLUENCE OF TRANSFORMATIONAL LEADERSHIP STYLE AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE - Didis Kusnadi Sinaga; Bahdin Nur Tanjung (Proceeding International Seminar of Islamic Studies, 2022)
The purpose of this study was to determine and analyze the effect of transformational leadership and work motivation on performance at PT. Perkebunan Nusantara IV (Persero) Medan either partially or simultaneously. The approach used in this study is an associative approach. The population in this study were all employees of PT. Perkebunan Nusantara IV (Persero) Medan. The sample in this study using the slovin formula totaling 80 employees at PT. Perkebunan Nusantara IV (Persero) Medan. Data collection techniques in this study used interview techniques, documentation studies, observation, and questionnaires. The data analysis technique in this study uses Multiple Linear Regression Analysis Test, Hypothesis Testing (t Test and F Test), and Coefficient of Determination. The data processing in this study used the SPSS (Statistic Package for the Social Sciences) software program version 24.00. The results of this study prove that partially and simultaneously transformational leadership and work motivation have a significant effect on employee performance at PT. Perkebunan Nusantara IV (Persero) Medan